1963
DOI: 10.2136/sssaj1963.03615995002700060039x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Cotton Bur Mulch and a Ridge‐Furrow System in Reclaiming Saline Soils by Rainfall

Abstract: A cotton bur mulch facilitated leaching of soluble salts by rainfall. Salt concentration was reduced in the surface 30 inches of soil to a level below that considered detrimental to growth of field crops. The high efficiency of salt removal by rainfall was attributed to flushing of salts from conducting pores when rains occurred combined with diffusion of salts from nonconducting to conducting pores between rains. Exchangeable Na percentage was also reduced to a low level. A ridge‐furrow system facilitated lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Also with evaporation, the salt was transported to and deposited on the soil surface. Similar results have been reported by Fanning and Carter ( 1963), Sandoval and Bentz ( 1966), and Heilman et al ( 1968).…”
Section: Discussionsupporting
confidence: 91%
“…Also with evaporation, the salt was transported to and deposited on the soil surface. Similar results have been reported by Fanning and Carter ( 1963), Sandoval and Bentz ( 1966), and Heilman et al ( 1968).…”
Section: Discussionsupporting
confidence: 91%
“…However, secondary succession on these sites in arid and semiarid regions is extremely slow due to low precipitation, soil disturbance, and contamination. Mulching may also reduce salinity by reducing evaporation and subsequent salt accumulation at the soil surface (Fanning andCarter 1963, Hamilton 1972). Screening potentially useful materials in the field is of critical importance (O'Leary 1984).…”
Section: Cals Normal Disposal Rates Of 10 Drilling Fluid Components mentioning
confidence: 99%
“…A satisfactory crop was produced by this method. These investigators had shown earlier that cotton bur and wood chip mulches effectively reduced evaporation, increased water intake, and increased leaching of salts (FANNING and CARTER, 1963;CARTER and FANNING, 1964). RASMUSSEN et al (1972) have demonstrated that deep plowing of some salt affected soils brings about a complete reclamation.…”
Section: Crop Stand Establishmentmentioning
confidence: 99%